Mediterranean diet adherence and epilepsy: the mediating role of stroke based on a cross-sectional study - Mingjing Zhou; Xuyan Zhao; Peinan Liu; Xiangwei Hou; Yiyang Cao; Maode Wang; Jia Wang (European Journal of Medical Research)
Abstract Background Epilepsy is a neurological disorder that can affect individuals of all genders and ages. Recent studies have indicated that the Mediterranean diet exerts a neuroprotective effect through its anti-inflammatory and antioxidant properties in non-Mediterranean regions. However, the association between the Mediterranean diet and epilepsy requires further elucidation. Methods A total of 14,259 participants were enrolled in this study from the National Health and Nutrition Examination Survey (NHANES) database, spanning the period from 2013 to 2018. Weighted logistic regression analysis assessed the association between Mediterranean diet adherence and epilepsy. Random forest analysis was conducted to evaluate the relative importance of diet components. Furthermore, mediation analysis with bootstrapping was employed to explore the mediating role of epilepsy. Results After adjusting for all potential covariates, higher Mediterranean diet adherence was associated with a lower risk of epilepsy (OR = 0.50, 95% CI 0.27–0.95, P = 0.033). Moreover, whole grain was identified as a pivotal component. Mediation analysis revealed that stroke functioned as a potential mediating factor in the association between Mediterranean diet adherence and epilepsy (mediation proportion = 6.49%, P = 0.034). In addition, interaction analysis suggested an interaction between the Mediterranean diet and diabetes (P = 0.029). Conclusions These novel findings suggested that higher adherence to the Mediterranean diet was linked with a lower risk of epilepsy, with stroke having a potential mediating role in the association. Promoting the Mediterranean diet may be a strategy for epilepsy management, supporting the need for further longitudinal studies.